2022
DOI: 10.3390/nu14101992
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of the Action of Vitamin D and Silicon Chelates in Bone Fracture Healing and Bone Turnover in Mice and Rats

Abstract: This study presents findings on the biological action of an integrated supplement containing the following components involved in osteogenesis and mineralization: vitamin D and silicon in the bioavailable and soluble form. A hypothesis that these components potentiate one another’s action and make calcium absorption by the body more efficient was tested. Biological tests of the effect of vitamin D and silicon chelates on bone fracture healing and bone turnover were conducted using ICR mice and albino Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Rats were the most common animal studied (n = 18 treatments), followed by chicks (n = 13 treatments) and horses (n = 6 treatments), with mice (n = 4 treatments), calves (n = 2 treatments), pigs (n = 2 treatments), and turkeys (n = 1 treatment) making up the rest of the experiments. Two papers [26,36] each included two experiments with two different species. Overall mean ± standard deviations, as well as minimums, maximums, and medians for total standardized Si, Si supplementation amounts, and dietary Si intake, are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Rats were the most common animal studied (n = 18 treatments), followed by chicks (n = 13 treatments) and horses (n = 6 treatments), with mice (n = 4 treatments), calves (n = 2 treatments), pigs (n = 2 treatments), and turkeys (n = 1 treatment) making up the rest of the experiments. Two papers [26,36] each included two experiments with two different species. Overall mean ± standard deviations, as well as minimums, maximums, and medians for total standardized Si, Si supplementation amounts, and dietary Si intake, are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems reasonable to suggest that some forms of hip fracture in older populations that are often not treated for possible osteoporotic risk 24 may derive some independent or collective benefit from vitamin D supplementation as far as reducing hip fracture incidence rates as well as mortality rates or further fractures post hip fracture surgery in vulnerable older adults. [24][25][26][27][28] In combination with silicon a recent basic study has revealed some degree of vitamin D influence on bone structure restoration and improved calcium absorption that appears to offer a possible avenue for enhancing bone related regeneration and that may prove valuable to examine further in the realm of hip fracture prevention and that is supported by human clinical evidence, [29][30][31][32] even though its presence may not impact number of falls or injurious falls that often lead to hip fractures. 33 However, there are multiple contrary study findings as well as multiple design problems that remain in this body of research, even though more favorable potentially relevant clinical findings prevail than not.…”
Section: Specific Observationsmentioning
confidence: 99%